Effects of myo-inositol plus alpha-lactalbumin in myo-inositol-resistant PCOS women - Mario Montanino Oliva; Giovanna Buonomo; Marco Calcagno; Vittorio Unfer (BMC, 2018)
Abstract Background Myo-inositol (MI), successfully used in polycystic ovary syndrome (PCOS), was administered with α-LA to exploit its action of favouring the passage of other molecules through biological barriers, and also considering its anti-inflammatory effect. Methods PCOS patients, according to the Rotterdam ESHRE-ASRM criteria, with anovulation and infertility > 1 year, were included in this open and prospective study. The preliminary phase was aimed at determining a set of MI-resistant PCOS patients. This treatment involved 2 g MI, taken twice per day by oral route, for three months. The Homeostasis Model Assessment (HOMA) index and MI plasma levels were measured. In the main phase, previously selected MI-resistant patients received the same daily amount of MI plus 50 mg α-LA twice a day, for a further three months. Ovulation was assessed using ultrasound examination on days 12, 14 and 20 of the cycle. The HOMA index, lipid, hormone and MI plasma levels were detected at baseline and at the end of this phase. Results Thirty-seven anovulatory PCOS subjects were included in the study. Following MI treatment, 23 of the 37 women (62%) ovulated, while 14 (38%) were resistant and did not ovulate. In the latter group, MI plasma levels did not increase. These MI-resistant patients underwent treatment in the main phase of the study, receiving MI and α-LA. After this combined treatment, 12 (86%) of them ovulated. Their MI plasma levels were found to be significantly higher than at baseline; also, a hormone and lipid profile improvement was recorded. Conclusion The combination of MI with α-LA allowed us to obtain significant progress in the treatment of PCOS MI-resistant patients. Therefore, this new formulation was able to re-establish ovulation, greatly increasing the chances of desired pregnancy. Trial Registration Clinical trial registration number: NCT03422289 (ClinicalTrials.gov registry).